Sistem Informasi Medical Record Pasien Pada Puskesmas Sudu Kec. Alla Kab. Enrekang Berbasis Website - Yuanita B; M Miftach Fakhri; Wahyu Hidayat (Program Studi Teknik Komputer, 2021)
The development of information technology has encouraged humans to complete their routine tasks quickly and efficiently. The work in the service department of puskesmas Sudu is already very dense where the puskesmas has a staff of 67 people, 1 general practitioner, 1 dentist and ±2,530 medical card members from each head of the family. While the mutilation of patient medical records carried out by the medical services department at puskesmas Sudu is still manual. This research was carried out with the aim that the recording of medical records resulting from patient consultations is better recorded and efficiency no longer uses conventional means but has been computerized, so that when data is needed at any time it will be easy in the search. The type of research used is a type of qualitative research, using data collection methods, namely observation, interviews and literature studies where the strategy used is design and creation. This medical record information system was developed using PHP and MySQL programming languages with dreamwaver media editor as well as application testing using the Black Box method. From this study resulted in the design and application of a website-based patient medical record information system at the Puskesmas Sudu Kec. Alla Kab. Enrekang, which can be used as a tool to facilitate medical record officers in the presentation of information and processing patient disease data.